ANALISIS PENGARUH MOTIVASI TERHADAP KINERJA APARAT PEMERINTAH KELURAHAN PALLAMEANG KABUPATEN PINRANG - Ahmad Musseng (AkMen JURNAL ILMIAH, 2017)
This study aims to determine the influence of motivational factors on the performance of government officials and village Pallameang Pinrang to determine the motivating factors which most affect the performance of village officials Pallameang Pinrang. The research object is the Village government officials Pallameang Pinrang. The sample is a whole apparatus of 16 people. The analysis used is multiple linear regression analysis. The results of the analysis concluded that together all of the variables that incentives, awards, work environment, education and training positive and significant impact on the performance of government officials Village Pallameang Pinrang. The most influential variable is the provision of incentives.